2014
DOI: 10.1155/2014/497278
|View full text |Cite
|
Sign up to set email alerts
|

The Dyeing Procedures Evaluation of Wool Fibers withPrangos ferulaceaand Fastness Characteristics

Abstract: In this study, the dyeing procedure of wool fibers withPrangos ferulaceawas evaluated and optimized by response surface methodology (RSM). Using this method, the quantitive relationship between dye concentration ofPrangos ferulacea, mordant concentration, dyeing temperature, and dyeing time on the dyeing procedure was investigated. The effect of these variables as well as plasma pretreatment was examined on the color strength of dyed samples. Finally, the fastness characteristic of dye sampled at proposed opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This investigation was focused on the ability of an aqueous and alcoholic extract of S.vulgare, acting as a natural dye, to carry out the dyeing of 100 % wool jersey knit samples under the influence of different conditions [5,6,7]. The color strength and washing fastness were then thoroughly investigated.…”
Section: Dyeing Processmentioning
confidence: 99%
“…This investigation was focused on the ability of an aqueous and alcoholic extract of S.vulgare, acting as a natural dye, to carry out the dyeing of 100 % wool jersey knit samples under the influence of different conditions [5,6,7]. The color strength and washing fastness were then thoroughly investigated.…”
Section: Dyeing Processmentioning
confidence: 99%
“…They found that the application of plasma and acetylated lecithin improved the color strength significantly; however, unsatisfactory results were obtained for hydroxylated-acetylated lecithin indicated from the lower K/S values of madder dyed wool. Barani and Rahimpour reported the dyeing properties of Prangos ferulacea on wool substrate using response surface methodology (RSM) for optimization of various variables. The effect of plasma pretreatment and other variables such as dye concentration, mordant concentration, dyeing temperature, and time on color strength and fastness properties was also investigated.…”
Section: Irradiation Technologiesmentioning
confidence: 99%
“…In the recent decade, there has been a renewed interest to use environmentally friendly products (Tiwari et al , 2019). Natural dyes, because of their nontoxic, energy-saving, biodegradable nature, health and safety aspects, have been receiving increasing attention from researchers (Kasiri and Safapour, 2014; Barani and Rahimpour, 2014; Salem et al , 2013). Natural dyes are derived from natural sources such as plants, animals, minerals and microbial (Rahman Bhuiyan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that an increase in the dyeing time and mordant concentrations lead to higher color strength value. Plasma pretreatment of wool fiber enhances Prangos ferulacea dye uptake of wool fibers (Barani and Rahimpour, 2014).…”
Section: Introductionmentioning
confidence: 99%